Analisis Perjodohan Di Pondok Pesantren Perspektif Hukum Islam (Studi Pondok Pesantren Salafiyah Shirothul Fuqoha’) - Najib, Mohammad Ainun; Ulum, Bahrul (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
Marriage is the longest form of worship in a person's life and is one of the most desired things by every human being. Therefore, it must be prepared earnestly. Among the many preparations that need attention, one of the most important is choosing a partner. Choosing a partner is a determining factor in the household that will be built. One method of choosing a partner is through matchmaking. Matchmaking not only occurs in society at large but also within pesantren where the Kiai often plays the main role in arranging marriages for the students. This research aims to analyze the practice of matchmaking as well as the Islamic legal perspective on it. This study is categorized as field research, which will be conducted directly using a normative-empirical approach. The data collection techniques used are interviews and documentation. The sources of data include both primary and secondary sources. The primary data consists of interviews with the Kiai who arranges the matches as well as the individuals involved in the matchmaking process. The secondary data serves to support the primary sources and includes books and articles related to the topic. The findings of this research explain that the matchmaking practice in Pondok Pesantren Salafiyah Shirothul Fuqoha’ begins with a respectful visit to a kiai and being summoned, followed by a meeting. Due to the students' obedience to the kiai, most of them accept the matchmaking proposed by him. The students being matched are usually those who have completed their studies, serve in the pesantren, and are considered ready for marriage. From the perspective of Islamic law, this matchmaking practice aligns with the principles of Islam and falls under the category of maslahah tahsiniyah, indicating that such matchmaking is acceptable and justified by local customs and brings positive impacts to the households that are formed.